DAMPAK BULLYING TERHADAP PRESTASI BELAJAR SISWA DI SD NEGERI 35 PALEMBANG - suginah; Yasir Arafat; Eni Heldayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted with the aim of determining the impact of bullying on student achievement at SD Negeri 35 Palembang. The method used in this study is a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation. The subjects in this study were several students who were victims of bullying , class teachers, and homeroom teachers at SD Negeri 35 Palembang. Data analysis used the Miles and Huberman interactive model which includes data reduction, data presentation, and drawing conclusions. The results of the study showed that bullying that occurred, both verbally and non-verbally, had a negative impact on students' enthusiasm for learning, concentration, and academic results. Students who were victims of bullying tended to experience decreased interest in learning, low self-confidence, and decreased learning achievement. Thus, it can be concluded that bullying has a significant impact on decreasing student learning achievement at SD Negeri 35 Palembang